3D printing surimi enhanced by surface crosslinking based on dry-spraying transglutaminase, and its application in dysphagia diets. (July 2023) - Zhu, Juncheng; Cheng, Yang; Ouyang, Zhiying; Yang, Yuxin; Ma, Liang; Wang, Hongxia; Zhang, Yuhao
Abstract: Dry-spraying transglutaminase (TG) was explored as surface modification agent for enhancing the surimi structures and promoting its practical 3D printing application. Glycerol functionalization, 3D extruding critical parameters, TG based surface crosslinking, practical cooking loss, and innovative applications of 3D-printed surimi were investigated. Rheological performances (shear ramp, strain sweep and thixotropy tests) indicate that glycerol could enhance excellent pseudo plasticity (fluid behavior index n < 1), high mechanical strength & strain resistance (high G′, and wide linear viscoelastic region 2.51%), and outstanding thixotropy (high recovery rates, up to 61.47%) of surimi, owing to that glycerol could promote the hydration of surimi myosin and prevent protein aggregation by stabilizing aggregation-prone intermediates. The further optimization of the extruding parameters (nozzle diameter 1.00 mm and "Rectilinear" filling structure) would improve the surimi dimensional printing deviations, and increase surimi gel strength (up to 22.29 g mm) by regulating interlayer bonding zones. Compared with chemical crosslinking agents NaCl and CaCl2 for modifying surimi, surface crosslinking based on dry-spraying TG would better raise the printable height efficiency (97.50%), improve the surimi texture, and enhance suitable water distribution, resulting in fine and dense network by hydrophobic interactions, disulfide bonds and non-disulfide covalent bonds. Subsequently, the cooking loss tests and International Dysphagia Diet Standardization Initiative tests proved that 3D-printed surimi could be classified as a potential transitional food for dysphagia groups. Surface crosslinking based on dry-spraying TG suggests a bright promise in practical high-accuracy, sophisticated 3D printing of surimi and holds potential in dysphagia diets and innovating food products. Graphical abstract: Image 1 Highlights: Glycerol prevents protein aggregation and enhances rheological properties of surimi. Rectilinear improves the printing deviation due to the criss-cross infill structure. Dry-spraying transglutaminase boosts the printed structure by surface crosslinking. 3D-printed surimi shows high shape retention and shape stability with dense network. The innovative 3D-printed surimi is potential transitional food in dysphagia diets.